Вплив інтенсивних технологій на агроекологічний стан ґрунтів Волині - Ясенчук, Неля; Зінчук, Микола; Iasenchuk, Nelia; Zinchuk, Mykola (Східноєвропейський національний університет імені Лесі Українки, 2016)
Акцентовано увагу на господарських й агроекологічних балансах за активного впровадження інтенсивних технологій рослинництва у Волинській області. Виявлено загальні негативні тенденції стосовно показників родючості ґрунтів, недостатніх рівнів застосування органічних і мінеральних добрив, а також обернені до них господарські результати, що характеризуються зростанням урожаїв. Піднято проблему невідповідності реальної ситуації в агровиробництві фундаментальним науковим положенням та висловлено припущення про порушення рівноваги агроекосистем компонентами запроваджених технологій. The attention has been paid to the economic and agro-ecological balances under the conditions of the active implementation of the crop intensive technologies in the Volyn region. General negative tendencies of the indicators of the soil fertility and insufficient usage of organic and mineral fertilizers were described. The economic results that are characterized by the rising harvests were pointed out too. The problem of the discrepancy of the actual situation in the agricultural production with fundamental scientific principles was pointed out. Although the implementation is intensive technologies and production capacity, while fixed dangerous depletion of soil degradation processes against the background of insufficient provision of agrochemical and agrobiological resources.
Influence of the Intensive Technologies on the Agro-ecological Condition of the Soils of Volyn
Keywords: інтенсивні технології; баланс гумусу й поживних речовин; мінеральні та органічні добрива; урожайність; родючість; ґрунт; intensive technologies; a balance of humus and nutrients; mineral and organic fertilizers; fertility; yield; soil